Probing defects in ZnO by persistent phosphorescence - Ye Honggang (Institue of Optics and Electronics, Chinese Academy of Sciences, 2018)
Native point defects in ZnO are so complicated that most of them are still debating issues, although they have been studied for decades. In this paper, we experimentally reveal two sub-components usually hidden in the low energy tail of the main broad green luminescence band peaking at 547 nm (~2.267 eV) in intentionally undoped ZnO single crystal by selecting the below-band-gap (BBG) optical excitations (e.g. light wavelengths of 385 nm and 450 nm). Moreover, both sub-components are manifested as long persistent phosphorescence once the BBG excitations are removed. With the aid of a newly developed model, the energy depths of two electron traps involved within the long lived orange luminescence are determined to be 44 meV and 300 meV, respectively. The candidates of these two electron traps are argued to be most likely hydrogen and zinc interstitials in ZnO.